2018
DOI: 10.1111/jth.14202
|View full text |Cite
|
Sign up to set email alerts
|

Learning by counting blood platelets in population studies: survey and perspective a long way after Bizzozero

Abstract: Platelet count represents a useful tool in clinical practice to discriminate individuals at higher risk of bleeding. Less obvious is the role of platelet count variability within the normal range of distribution in shaping the individual's disease risk profile. Epidemiological studies have shown that platelet count in the adult general population is associated with a number of health outcomes related to hemostasis and thrombosis. However, recent studies are suggesting a possible role of this platelet index als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…It is known that platelet counts are determined by several factors and decline with age, and that women have higher platelet counts than men [ 16 , 51 , 59 , 60 , 61 , 62 , 63 , 64 ]. For every 10 years, Santimone et al reported a sex-adjusted decline of 10 × 10 9 /L [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that platelet counts are determined by several factors and decline with age, and that women have higher platelet counts than men [ 16 , 51 , 59 , 60 , 61 , 62 , 63 , 64 ]. For every 10 years, Santimone et al reported a sex-adjusted decline of 10 × 10 9 /L [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Platelet indices are extensively used as diagnostic and prognostic markers in several human pathological conditions. In particular, platelet count (Plt) and mean platelet volume (MPV) are assessed in clinical and population studies, often combined, as markers of platelet function [1]. In addition to the measurement of MPV, optical hematocytometry counters and automated measurements of impedance have allowed definition of the platelet distribution width (PDW), which is a volume parameter, measured as the difference between the highest and the lowest platelet volume, at 20% relative height in the platelet-size distribution histogram [2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to adhering to a self-management regimen, current literature suggests there are many determinants of self-management adherence. Evidence suggests that social resources, such as support from family, friends, and formal/informal support groups, can improve self-management adherence across chronic conditions (Dwarswaard, Bakker, van Staa, & Boeije, 2016; McDonald, Slavin, Pitts, & Elliott, 2015; Taylor et al, 2014). Higher levels of social resources, specifically social capital, has shown to improve medication adherence and quality of life in PLWH (Webel, Sattar, Schreiner, & Phillips, 2016).…”
Section: Introductionmentioning
confidence: 99%